PENGARUH HOSPITALITY PUSTAKAWAN DAN SERVICE DIFFERENTIATION TERHADAP KINERJA LAYANAN PERPUSTAKAAN UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Haloho, Elizabeth; Harefa, Hilda Syaf’aini; Siagian, Ernita (Jurnal Manajemen dan Bisnis, 2024)
This research aims to determine the influence of librarian hospitality and differential service both partially and simultaneously on the service performance of the Santo Thomas Catholic University Medan Library. The population in this study was 7,292 active students for the 2023/2024 academic year. The sample in the study was 99 respondents using the Simple Random Sampling technique. The analytical methods used are instrument tests, classical assumption tests, hypothesis tests, coefficient of determination tests and multiple linear regression analysis. The research results show (1) Based on the Partial Test (t Test) librarian hospitality has a positive and significant effect on the service performance of the Santo Thomas Catholic University Medan Library, (2) Based on the Partial Test (t Test) Service differentiation has a positive and significant effect on the service performance of the University Library Santo Thomas Catholic Medan, and (3) Based on the Simultaneous Test (F Test) of librarian Hospitality and Service differentiation simultaneously on the service performance of the Santo Thomas Medan Catholic University Library.